Integration of Islamic values and science in integrated Islamic boarding school-based Islamic schools - Asman Asman; Muliani Muliani; Amin Amin (Edusoshum : Journal of Islamic Education and Social Humanities, 2025)
Education in integrated Islamic boarding schools seeks to integrate Islamic values with science to create a balance between spiritual and intellectual aspects. This study aims to analyze the effectiveness of integrative education models in improving students' academic understanding and Islamic character. Using a qualitative method through a case study in one of the integrated Islamic boarding schools, data was collected through observation, interviews, and document analysis. The results of the study show that this integrative approach is able to improve the quality of learning, strengthen Islamic values in daily life, and build synergy between science and Islamic teachings in the pesantren education environment. In addition, this model also encourages students to be more active in developing critical and reflective thinking skills in facing global challenges. The implementation of this approach also has an impact on increasing students' motivation to learn and creating a more conducive academic environment based on Islamic values.